P518 Cardiovascular Risk Factors in Adolescents with inflammatory bowel disease: A Cross-sectional Population-Based Study. (25th January 2019) - Ghersin, I; Katz, L H; Daher, S; Shamir, R; Assa, A
Abstract: Background: There is conflicting evidence regarding the association of inflammatory bowel disease (IBD) with increased risk for cardiovascular diseases (CVD). We aimed to investigate the association of IBD with cardiovascular risk factors including obesity, blood pressure (BP) and resting heart rate (RHR) at late adolescence in a large cross-sectional population-based study. Methods: A total of 1144213 Jewish Israeli adolescents who underwent a general health examination from 2002 to 2016 were included. A definite diagnosis of IBD was based on accepted criteria. Covariate data included demographic measures, height, weight, BMI, blood pressure, resting heart rate, and risk factors associated with CVD. Results: Overall, 2372 cases of IBD were identiﬁed out of 1144213 persons examined (0.2%). Crohn's disease (CD) accounted for 68% of IBD cases. Systolic hypertension was significantly less common among CD subjects (OR, 0.67; 95% CI 0.56–0.81, p < 0.0001), while no significant differences were observed for diastolic hypertension. The rates of hypertension among ulcerative colitis (UC) patients were similar to those of the control group. The proportions of overweight and obese subjects were significantly lower among CD patients, while no significant differences were observed between UC patients and the control group. Congenital hypercoagulable state (OR, 16.9; 95% CI 8–35.7, p < 0.0001) was significantly more common in subjects with CD, but not among subjects with UC. On the other hand, we did not detect significant differences in the risk for non-congenital venous thromboembolism. Insulin-dependent diabetes mellitus, noninsulin-dependent diabetes mellitus and hyperlipidaemia were not more common among IBD patients. Conclusions: There appears to be an association between CD and congenital hypercoagulable state. The prevalence of traditional cardiovascular risk factors, however, including diabetes mellitus, hyperlipidaemia and hypertension, was not increased among subjects with IBD.